A model for predicting attitudes towards spanish product, brands and country image: An exploratory international study - Cerviño, Julio; Rivera Camino, Jaime Eduardo (CENTRUM Publishing, 2015)
This article aims to respond to recent demands for more in-depth study on how consumers use brand-associated images to shape their attitudes to buying. A multi-attribute design is used to analyze how certain variables among buyers (ethnocentrism and similarity) are related to brand images (country and product) in the formation of attitudes within an international context. This research is based on a sample of 215 international experts from 31 countries whose responses were analyzed with structural equation modeling. The results obtained have implications for academics, government officials and directors of international marketing. Among the contributions made by the present study is its attempt to clarify the existing literature regarding the causes and effects of brand images and, as well, the measures it develops to make certain key variables (as indicated in the literature) operational.
Keywords: Attitudes; Brand image; Country brand; Product brand; Ethnocentrism; Similarity; Spanish image; http://purl.org/pe-repo/ocde/ford#5.02.04